A Review of the Academic Engagement of Medical Students in Kerman University of Medical Sciences Iran 20112012 - Esmat Noohi; Hamideh Montazeri; Mostafa Shokohi (Kerman University of Medical Sciences, 2015)
Background & Objective: The concept of active engagement or academic engagement is a certain understanding of the relationship between students and the university The university is an environment that provides learning opportunities that will lead to student learning The nature and level of learning depends on the students way of using their environmental resources Positive engagement and an interactive supportive academic environment are essential elements in success in the learning process On the other hand isolation alienation and passiveness of students results in their academic failure The aim of the present study was to investigate academic engagement of medical students of Kerman University of Medical Sciences Iran in 20112012 In this study 2 domains of academic engagement were investigated (active and participatory learning and level of academic challenge)   Methods: In this descriptiveanalytical crosssectional study all medical students of Kerman University of Medical Sciences were recruited using stratified random sampling method The data collection tool was the National Survey of Student Engagement (NSSE)   Results: In this study 211 medical students from different academic years with the average age of 226 ± 31 were enrolled The mean active engagement score of the students was 9864 ± 3233 Active and cooperative learning was at a significant level based on all demographic variables except employment The active and cooperative learning of male students differed significantly from that of female students married students from single students different academic years and native from local students Moreover students who were members of one of the academic centers had significantly higher active and participatory learning scores Mean active and participatory learning and level of academic challenge were 174 ± 56 and 217 ± 71 respectively Both domains were reported as unsatisfactory among students   Conclusion: The results showed the unsatisfactory academic engagment status of the students of the Kerman University of Medical Sciences Thus it is hoped that with future planning to use more modern teaching methods which have a higher level of academic challenges and active and collaborative learning and by the appropriate support of the university university staff and faculty members we are able to take steps toward the improvement of academic engagement and thereby student success